Underestimation of travel-associated risks by adult and paediatric travellers compared to expert assessment: A cross-sectional study at a hospital-based family pre-travel clinic. Issue 47 (May 2022) - Piché-Renaud, Pierre-Philippe; Hoang Nguyen, Jenny; Pell, Lisa G.; Wei Ma, Xiao; Alattas, Nadia; Khan, Sarah; Schwartz, Kevin L.; Farrar, Daniel S.; Akseer, Nadia; Lam, Ray E.; Louch, Debra; Science, Michelle; et al.
Abstract: Background: Travellers' perception of their risk for acquiring travel-related conditions is an important contributor to decisions and behaviors during travel. In this study, we aimed to assess the differences between traveller-perceived and expert-assessed risk of travel-related conditions in children and adults travelling internationally and describe factors that influence travellers' perception of risk. Methods: Children and adults were recruited at the Hospital for Sick Children's Family Travel Clinic between October 2014 and July 2015. A questionnaire was administered to participants to assess their perceived risk of acquiring 32 travel-related conditions using a 7-point Likert scale. Conditions were categorized as vector-borne diseases, vaccine-preventable diseases, food and water borne diseases, sexually transmitted infections and other conditions. Two certified travel medicine experts reviewed each patient's chart and assigned a risk score based on the same 7-point Likert scale. Traveller and expert risk scores were compared using paired t-tests. Results: In total, 207 participants were enrolled to participate in this study, 97 children (self-reported, n = 8; parent-reported, n = 89), and 110 adults. Travel-related risk for adults and parents answering for their children were significantly underestimated when compared to expert-assessed risk for 26 of the 32 assessed conditions. The underestimated conditions were the same for both adults and parents answering for children. Travel-related risk was not over-estimated for any condition. Conclusions: Adults underestimated their children's and their own risk for most travel-related conditions. Strategies to improve the accuracy of risk perception of travel-related conditions by travellers are needed to optimize healthy travel for children and their families. Highlights: Understanding travellers' perception of risk is key for pre-departure counselling. Adults underestimate their child and their own risk of travel-acquired conditions. A large proportion of travel-acquired conditions are unknown to travellers.